198k views
5 votes
X - y= -4 -2x +3y =6

User Mellowg
by
6.2k points

1 Answer

5 votes

Answer:

x=-6, y=-2, (As a point) (-6, -2).....The point form is not necessary unless you want to solve the system (of equations) by graphing.

Explanation:

By substitution:

x-y=-4 By adding y on both sides,

x=y-4

Now you can substitute x for the expression (y-4)

Plug the (y-4) as x in the other equation.

So -2x+3y=6 becomes

-2(y-4)+3y=6

Now solve:

-2(y-4)+3y=6 distributes out to be

-2y+8+3y=6 Now combining like terms

y+8=6 Subtract 8 on both sides to isolate the variable

y=-2

Now plug the value -2 in where the y is in any equation (preferably the easier/less complicated one) and solve for x.

So x-y=-4 becomes

x-(-2)=-4

=x+2=-4

=x=-6

User Oliver Nightingale
by
6.3k points